Analisis pengaruh variasi elektroda las e6013 dan e7018 terhadap kekuatan tarik dan kekerasan pada bahan baja ss 400 - Shomad, M. Abdus; Shahar Mushfi, M. (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2017)
Development of technology in the field of construction is increasingly advanced today, will not be separated from technology or welding techniques because it has a very important role in engineering and metal repairs.This study aims to determine the effect of electrode to tensile strength and hardness of SMAW welding on SS 400 steel. The material is given welding treatment with electrode variation E6013 and E7018 diameter of 3.2 mm by using SMAW DC reverse polarity ie the electrode holder is connected to positive pole and the parent metal is connected With a negative pole. The type of camp used is V. The highest tensile strength occurred in the specimens of raw materials that amounted to 432.49 MPa which increased by 10.41 MPa from group E7018. The highest yield strength occurred in the raw materials specimens of 308.53 MPa which had an increase of 9.31 MPa from the E7018 electrode variation group. The highest hardness level occurs in the weld metal part of E7018 electrode variation group that is equal to 189.6 kg /mm2.